Analysis of the effect of organic supplements on the growth of Chrysanthemum explants (Chrysanthemum sp.) in tissue culture media - Haris, Abdul; Abdullah, Abdullah; Aminah, Aminah; Akbar, Abdul; Dindasari, Dita (Agrovigor, 2024)
Chrysanthemum (Chrysanthemum sp.) is an ornamental plant of high economic value with a continuously increasing demand, necessitating efficient production methods. Tissue culture techniques are one of the solutions that enable rapid and disease-free plant propagation. This study aims to evaluate the effect of organic supplements on the growth of chrysanthemum explants. The research was conducted using a completely randomized design with six treatments, namely control (without supplements), banana extract, corn seed extract, coconut water, and combinations of coconut water with banana and corn seed extracts. The results show that the banana extract supplement at a concentration of 50 g/L provides the best growth in terms of plantlet height, number of leaves, and roots compared to other treatments. The combination of coconut water and banana extract also significantly enhances growth. This study concludes that the use of organic supplements can improve the efficiency of chrysanthemum propagation through tissue culture, supporting more sustainable ornamental plant production.